The quest for democratic bliss: Which dimensions hold the key? - Ņikišins Jurijs (Filozofija i Društvo, 2025)
The majority of Europeans value living in a country governed by democratic principles. It is argued that the evaluation of democracy and satisfaction with it are pivotal for ensuring its functioning and sustainability. When asked about the importance of specific indicators of democracy, such as free and fair elections, equality before the courts, and freedom of the press, most respondents assign a high and comparable level of importance to each. However, the overall significance of democracy and its dimensions does not necessarily reflect the perceived quality of democracy within a given nation. To explore the determinants of satisfaction with the state of democracy while accounting for cross-national variation, a multilevel regression analysis is conducted, examining the impact of various factors on four dimensions of democratic evaluation - electoral, liberal, social, and direct - using comparative data from the ESS Round 10 Understandings and Evaluations of Democracy module. The results reveal significant disparities across dimensions of democracy, with Nordic countries leading and some Western Balkan and Eastern European countries lagging. They also underscore complex relationships between political efficacy and evaluations of democracy, showing a positive association with external efficacy, particularly in countries with higher political rights, and a negative association with internal efficacy, which diminishes in contexts of greater civil liberties.